Time course of action of two inhaled corticosteroids, fluticasone propionate and budesonide. Issue 1 (23rd December 2003) - Phillips, K; Oborne, J; Lewis, S; Harrison, T W; Tattersfield, A E
Abstract : Background: It is important to be able to compare the efficacy and systemic effects of inhaled corticosteroids but their slow onset of action makes it difficult to measure the maximum response to a given dose. Submaximal responses could be compared if the time course of action of the inhaled corticosteroids being compared was similar. We have compared the time course of action of fluticasone and budesonide, measuring response as change in the provocative dose of adenosine monophosphate causing a 20% fall in forced expiratory volume in 1 second (PD20 AMP). Methods: Eighteen subjects with mild asthma, aged 18–65, took part in a three way randomised crossover study. Subjects took fluticasone (1500 μg/day), budesonide (1600 μg/day), and placebo each for 4 weeks with a washout period of at least 2 weeks between treatments; PD20 AMP and forced expiratory volume in 1 second (FEV1 ) were measured during and after treatment. The time taken to achieve 50% of the maximum response (T50%) was compared as a measure of onset of action. Results: There was a progressive increase in PD20 AMP during the 4 weeks of treatment with both fluticasone and budesonide but not placebo; the increase after 1 and 4 weeks was 2.28 and 4.50 doubling doses (DD) for fluticasone and 2.49 and 3.65 DD for budesonide. T50% was 9.3 days for fluticasone and 7.5 days for budesonide with a median difference between fluticasone and budesonide of 0.1 days (95% CI −1.4 to 2.65). There was a wide range of response to both inhaled corticosteroids but good correlation between the response to fluticasone and budesonide within subjects. FEV1 and morning peak expiratory flow rate (PEFR) increased during the first week of both active treatments and were stable thereafter. There was a small progressive improvement in nocturnal symptoms with both active treatments. Conclusion: PD20 AMP was a more sensitive marker of response to inhaled corticosteroid therapy than FEV1 and PEFR. The time course of action of fluticasone and budesonide on PD20 AMP is similar, suggesting that comparative studies of their efficacy using 1 or 2 week treatment periods are valid. When a new inhaled corticosteroid becomes available, a pilot study comparing its time course of action with that of an established corticosteroid should allow comparative studies to be performed more efficiently.